Bonding Relationship between Silicon and Germanium with Group 13 and Heavier Elements of Groups 14–16. Issue 22 (20th October 2020) - Agarwal, Abhishek; Bose, Shubhankar Kumar
Abstract: The topic of heavier main group compounds possessing multiple bonds is the subject of momentous interest in modern organometallic chemistry. Importantly, there is an excitement involving the discovery of unprecedented compounds with unique bonding modes. The research in this area is still expanding, particularly the reactivity aspects of these compounds. This article aims to describe the overall developments reported on the stable derivatives of silicon and germanium involved in multiple bond formation with other group 13, and heavier groups 14, 15, and 16 elements. The synthetic strategies, structural features, and their reactivity towards different nucleophiles, unsaturated organic substrates, and in small molecule activation are discussed. Further, their physical and chemical properties are described based on their spectroscopic and theoretical studies. Abstract : The fascinating chemistry of multiple bonding in heavier main group elements always remains a curious topic among chemists due to their intriguing structure and reactivity features. In this minireview, the recent development of multiple bonding (homoatomic & heteroatomic) in silicon and germanium with group 13 and heavier elements of groups 14–16 is summarized.